"Hiroshima mon amour" and "The Lover": in search of the story - Verdugo, Ana Belén (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Poetic language is not exclusive of writing, although it is through writing it can reach it maximum expression, being words the most solid bond to thinking. Poetic language is an updating of the symbol, therefore, aesthetics and image. It is in this game about the different ways of projecting thought on artistic expression, where intermedial and transmedial relations can be found. An example of it can be traced in both works by the French author Marguerite Duras; the film Hiroshima mon amourand the novel TheLover, about which this article intends to establish a comparison to show the thought-image interaction in poetic or artistic expression. Pointing to aspects apparently irreconcilable like the pairings reality and memory, personal and politics, past and present, masculine and feminine, desire and moral, or poetry and reason, this article explores the intention present in both works of disarticulating the assumed idea about these elements as opposed, to show them as equal parts of a whole.
Keywords: Intermediality, transmediality, poetic language, Marguerite Duras.